2020
DOI: 10.1038/s41598-020-74342-z
|View full text |Cite
|
Sign up to set email alerts
|

The daily resolved temperature dependence and structure of planktonic foraminifera blooms

Abstract: Planktonic foraminifera (PF) life cycles are highly sensitive to marine conditions, which are evolving rapidly due to anthropogenic climate change. Even though PF shells in the sedimentary record serve as prominent proxies of past ocean conditions, very little is still known about their life cycles, particularly in oligotrophic environments. Here, we present a full annual record of PF fluxes (> 63 µm) from the oligotrophic Gulf of Aqaba, northern Red Sea, sampled at daily timescales during 2015–2016 using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…This one-dimensional view of δ 13 C assumes that the depth ecology of planktonic foraminifera does not change and therefore paleohydrological changes drive stable isotope variations. Yet, studies based on extant foraminifera indicate that depth habitat can vary as a result of season, biogeography and environment (e.g., Jonkers and Kučera, 2017;Kretschmer et al, 2018;Taylor et al, 2018;Chernihovsky et al, 2020) as well as changes in life strategy (Darling et al, 2009). Additionally, studies of foraminifera species and across evolutionary lineages have shown changing depth habitats through evolutionary history (Norris et al, 1993;Coxall et al, 2000;Stewart et al, 2012).…”
Section: Measuring Functionality In Foraminifera Traitsmentioning
confidence: 99%
“…This one-dimensional view of δ 13 C assumes that the depth ecology of planktonic foraminifera does not change and therefore paleohydrological changes drive stable isotope variations. Yet, studies based on extant foraminifera indicate that depth habitat can vary as a result of season, biogeography and environment (e.g., Jonkers and Kučera, 2017;Kretschmer et al, 2018;Taylor et al, 2018;Chernihovsky et al, 2020) as well as changes in life strategy (Darling et al, 2009). Additionally, studies of foraminifera species and across evolutionary lineages have shown changing depth habitats through evolutionary history (Norris et al, 1993;Coxall et al, 2000;Stewart et al, 2012).…”
Section: Measuring Functionality In Foraminifera Traitsmentioning
confidence: 99%
“…This partly explains why, as mentioned in the introduction, the model of synchronised reproduction has been challenged by the absence of recordable signal in many sediment trap and plankton tow studies (Lončarić et al, 2005;Rebotim et al, 2017;Iwasaki et al, 2017;Greco et al, 2019;Lessa et al, 2020;Chernihovsky et al, 2020). However, the concept of the emergence of the canonical trajectory from a large background juvenile mortality was raised already in one of the first studies dedicated to the synchronisation concept in planktonic foraminifera (Bijma et al, 1990).…”
Section: The Canonical Reproductive Behaviour Emerging Among Other Reproductive Dynamicsmentioning
confidence: 99%
“…These appealing and logical schemes became widely adopted, so much that we almost omitted that the presented depictions of life cycles of most species were idealised, that they still required additional observations, and that there remains a host of problems and uncertainties challenging the presented models. Next to the discovery of active photosymbiosis (Takagi et al, 2019) in species whose hypothetical OVM trajectories extend below the photic zone, there have been numerous observations of stable vertical habitats in the plankton (Rebotim et al, 2017;Iwasaki et al, 2017;Greco et al, 2019;Lessa et al, 2020) as well as shell flux patterns in sediment traps (Lončarić et al, 2005;Chernihovsky et al, 2020), showing no evidence of OVM and reproduction synchronised by the lunar cycle. Even where plankton tow and sediment trap could be interpreted as indicative for cohort growth (synchronised reproduction), the timing of reproduction with respect to the lunar cycle appeared to vary within species and among species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We can assume that the high abundance of foraminifera during the same cruise sampling area could be the reason for the decline of phytoplankton production in the equatorial region of EIO, due to their preference for a herbivorous diet mainly on diatoms [22,27,47]. In contrast, high chlorophyll-a surface concentration corresponded to low planktonic foraminifera fluxes, which were reported from the northern Red Sea, Gulf of Aqaba (GOA) [48].…”
Section: Discussionmentioning
confidence: 93%